Theoretical modeling of magneto-Conductivity (MC) in dilute p-Si/SiGe/Si under magnetic fields - Mabchour Hamza; Kacimi Houda; Fennane Sara; ALtalqi Fatehi; Echchelh Adil (EPJ Web of Conferences)
In the present work, we consider magneto-conductivity behavior within a two-dimensional p-Si/SiGe/Si system. A theoretical model of magneto-conductivity with three important contributions is derived, namely, an account for the weak localization process, for electron-electron interaction effects, and for the Zeeman effect, which is taken into account only if a magnetic field is present. Further, theoretical values predicted by our model are compared with experimental magneto-conductivity values for a comparison of similarity and difference with experimental values. In our research, experimental data for p-Si/SiGe/Si were used, which has been previously collected by I. L. Drichko et al. [1] for supporting purposes.